Using structural equation modeling to examine the influence of family planning social norms on modern contraceptive use in Nigeria - Mandal, Mahua; Calhoun, Lisa M.; McGuire, Courtney; Speizer, Ilene S. (Frontiers in Sociology, 2022)
Despite high knowledge of family planning (FP) among Nigerian women, use of modern contraceptives remains low. While FP investments in Nigeria have been ongoing for decades, relatively little emphasis on contextual and structural factors may have contributed to low demand for and use of contraception. From 2009 to 2014, the Bill & Melinda Gates Foundation (BMGF) supported the Nigerian Urban Reproductive Health Initiative (NURHI) with the aim of increasing voluntary use of contraceptives among women ages 15–49 years in six Nigerian cities. A subsequent phase of NURHI was implemented in three states for the next 3 to 5 years. Using cross-sectional survey data from three cities (two exposed to NURHI, one not exposed), this study examines whether social norms around FP were related to women's use of modern contraception, and whether the relationship differed by varying levels of exposure to the program (i.e., by city). We identified three distinct FP social norms through factor analysis: norms around delaying first pregnancy; spacing or limiting pregnancies; and using contraception when the husband disagrees. Using structural equation modeling, we found that FP social norms are related to use of modern contraceptive methods, and the relationship varies by city and norm type. The observed differences suggest that this relationship depends on numerous factors at the individual, interpersonal and societal level, and this may include malleable factors influenced by the NURHI program.